Methodology for evaluation of the life cycle of buildings with a focus on the private sector - Renáta Schneiderová Heralová; Eduard Hromada; Jakub Holcman; Stanislav Vitásek (Acta Polytechnica CTU Proceedings, 2022)
The paper describes the innovative methodology for the evaluation of the life cycle of buildings, which will be used in construction projects of Skanska, or other construction companies, in selecting the optimal solution from the point of view of construction engineering and LCC. The aim is to help LCC to be perceived by construction practice as a topic that needs to be addressed at the beginning of each construction project. The quantification of life cycle costs based on relevant input data on the technical parameters of the construction, structural elements and equipment, the time period of incurring the related costs should be an important basis for the decision of the investor, designer and future user of the building also with regard to environmental and social aspects, and in particular the long-term economic consequences.